Rationality of the using of photochromotherapy in the complex treatment of acute intestinal infections in children - N. V. Gonchar; V. V. Kir’yanova; T. G. Lepikhina; I. V. Razd’yakonova; S. G. Grigor’ev; N. V. Skripchenko (Журнал инфектологии, 2018)
Aim. The objective of the study was to substantiate the rationality of using monochromatic polarized incoherent optical radiation  (photochromotherapy) on the abdomen as a supplement to the  standard program for the treatment of acute intestinal infections in  children.Material and methods. Twenty-six children with acute intestinal  infections from 6 months to 12 years old were observed during  inpatient treatment. In the comparison group (n = 11), children  received standard therapy, including diet therapy, rehydration,  sorbents, probiotics or prebiotics, as well as indications for etiotropic  drugs. In the main group, patients (n = 15) in addition to standard  therapy received photochromotherapy as an effect on the abdomen  with monochromatic polarized incoherent optical radiation from the  Bioptron apparatus with a blue filter at a distance of 5 cm labile along the bowel. The duration of photochromotherapy was 5 minutes, the course of treatment included 4-5 sessions 1 time per  day. The effectiveness of the therapy regimens used in the groups  was assessed by the duration of the disease, the length of inpatient  treatment, the dynamics of changes in the clinical blood test at the  time of discharge. Results. The advantage of the technique with the addition of  standard treatment of acute intestinal infections by photochromotherapy was established. In the main group of  patients, the duration of the disease was significantly shorter  (9,1±0,8 days) compared to the comparison group (10,2±1,5 days,  p=0,02) against the background of a significant decrease in the severity of inflammatory manifestations in the hemogram in form of  a decrease in thrombocytosis. Conclusion. The obtained data make it  possible to recommend the method of photochromotherapy in the  complex therapy of intestinal infections of various etiologies in  children older than 6 months.